Exploration of temperature stability of linearity and RF performance metrics for PGP negative capacitance FET. (1st March 2023) - Chaudhary, Shalini; Dewan, Basudha; Singh, Devenderpal; Sahu, Chitrakant; Yadav, Menka
Abstract: The present work focuses on investigating the performance of partial ground plane selective buried oxide negative capacitance (NC) field-effect transistor (NCFET) electrical properties at high temperatures. The performance of the device has been studied between the temperature of 300–400 K using the Landau–Khalatnikov equation with the Poisson's equation. In NCFET, ferroelectric material in the gate stack generates NC effect that enhances the device performance by the voltage amplification process. Doped H F O 2 is used as the ferroelectric material because of its high dielectric capacitance and reliable polarization rate. This work primarily focuses on examining the effects of temperature change on the device's dc performance metrics, analog/radio frequency performance parameters, and linearity performance parameters. Compared to kT/q, sub-threshold slope rises more rapidly as temperature rises and diminishing the ferroelectric effect after 350 K. Also reduced intrinsic delay at higher temperatures make the device an great option for ultra-low-power and high switching speed applications. Additionally, the proposed device performs better in terms of linearity at greater temperatures.